2014
DOI: 10.3389/fnhum.2014.00985
|View full text |Cite
|
Sign up to set email alerts
|

BDNF mediates improvements in executive function following a 1-year exercise intervention

Abstract: Executive function declines with age, but engaging in aerobic exercise may attenuate decline. One mechanism by which aerobic exercise may preserve executive function is through the up-regulation of brain-derived neurotropic factor (BDNF), which also declines with age. The present study examined BDNF as a mediator of the effects of a 1-year walking intervention on executive function in 90 older adults (mean age = 66.82). Participants were randomized to a stretching and toning control group or a moderate intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
174
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(195 citation statements)
references
References 97 publications
6
174
2
9
Order By: Relevance
“…To this family of proteins also belong NGF (nerve growth factor), NT3 and NT4 (neurotrophin 3 and 4). BDNF exerts its eff ects on the cognitive (Alesi et al, 2014) sphere through the abilities described above, and it is thought to infl uence learning (Leckie et al, 2014). Interestingly, an increase in BDNF aft er exercise is positively correlated with cognitive performance; this was also confi rmed recently by Van Dongen, Kersten, Wagner, Morris & Fernández (2016), who demonstrated that physical activity performed four hours aft er learning improves memory effi ciency, showing how the hippocampus improves its effi cacy in memory retention.…”
Section: Introductionmentioning
confidence: 65%
“…To this family of proteins also belong NGF (nerve growth factor), NT3 and NT4 (neurotrophin 3 and 4). BDNF exerts its eff ects on the cognitive (Alesi et al, 2014) sphere through the abilities described above, and it is thought to infl uence learning (Leckie et al, 2014). Interestingly, an increase in BDNF aft er exercise is positively correlated with cognitive performance; this was also confi rmed recently by Van Dongen, Kersten, Wagner, Morris & Fernández (2016), who demonstrated that physical activity performed four hours aft er learning improves memory effi ciency, showing how the hippocampus improves its effi cacy in memory retention.…”
Section: Introductionmentioning
confidence: 65%
“…It should be mentioned that due to genetic pleiotropy, both COMT and BDNF have been found to be associated with several other aspects of cognition beyond WM, including reaction time (Das et al, 2014), cognitive flexibility (Kang et al, 2013), aging-related cognitive degradation (Ghisletta et al, 2014; Voelcker-Rehage et al, 2015), executive function (Leckie et al, 2014; Sapkota et al, 2015), and neurocognitive deficits in people with schizophrenia (Ahmed et al, 2015) or Parkinson's disease (Khalil et al, 2016). Nevertheless, WM has been the main focus of the previous literature in this field.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, in a training protocol investigation, it was found that in older adults the basal BDNF concentrations were elevated in response to an aerobic training protocol. 38 Another training study found that despite an increase in VO 2peak and max workload there was no effect on resting BDNF concentrations. 39 Additionally, long-term aerobic exercise training has also been shown to increase the acute exercise-dependent BDNF response to an exercise bout.…”
Section: Discussionmentioning
confidence: 99%